Air-Gap Reduction and Antenna Positioning of an X-Band Bow Tie Slot Antenna on 2U CubeSats - Boutaina Benhmimou; Fouad Omari; Nancy Gupta; Khalid El Khadiri; Rachid Ahl Laamara; Mohamed El Bakkali (Yayasan Riset dan Pengembangan Intelektual (YRPI), 2024)
In this research work, a small size and wide-band Bow Tie slot antenna (BTSA) is proposed and optimized for use on an unlimited lifetime small-sized CubeSats at X-band. Interestingly, this paper introduces a graceful mechanism of integrating Bow Tie slot antennas on the bodies of small CubeSat configurations, which minimizes the antenna throwing from the satellite body and the whole CubeSat volume. The proposed approaches propose and analyze in detail how a small metallic part of a 2U CubeSat body improves the antenna performances around an operating frequency of 8.4 GHz. It maximizes the antenna gain simultaneously with the beamwidth angles at 8.4 GHz by suppressing the resulting back-lobes, which are re-directed outside the CubeSat box. These impacts are achieved by shifting a very small air-gap distance of only 1 mm between the back face of the BTSA dielectric and the CubeSat top face. The developed BTSA is lightweight and exhibits a unidirectional radiation pattern with a wide beamwidth angle of about 160° and a high gain of about 11.0 dBi at 8.4 GHz. The overall results with occupied size and volume are satisfactory for unlimited lifetime CubeSat missions at X-band such as UM5-Ribat and UM5-EOSAT of University Mohammed V in Rabat.